Alterações de linguagem em crianças com histórias de desagregação familiar: três estudos de caso - Silva, Cristiane Pequeno da (2007)
Background: The familiar disaggregation finishes provoking a fragility in the subjective constitution, signaled in different difficulties in the child, being that one related to language one more excellent them. This dissertation had for objective to describe some difficulties in the language of three children whose histories of life present episodes of familiar disaggregation, with data of recklessness, permanence in shelter houses or substitution of family. Method: a survey next to the Conselho Tutelar de São Roque of the children whose families had been taken care of by the council members during the year of 2005. Of available handbooks, only seven had been selected, in function of the age of the children. Anamnese was carried through one and the analysis of documentations for survey of histories, the direct comment of the general behaviors of the children and the application of a test of language verbal (Tipiti) for description of the linguistic uses and deduced level of development of the language. Results: it can be observed that it has a dependence of the other in the organization of the speech of the three children, a time who already would have to establish its with certain autonomy. Conclusion: the results indicate that the fragility in the familiar structure can compromise the constitution of the subjectivity and, obviously, to modify the development of the language in the children, a time who when they are seen to the edge of the other in the speech, appear a great difficulty in elaborating its proper one